Building Tax Culture, Compliance and Citizenship. - OECD. (Organization for Economic Cooperation & Development, 2021)
Widespread voluntary tax compliance plays a significant role in countries' efforts to raise the revenues necessary to achieve Sustainable Development Goals. As part of this process, governments are increasingly reaching out to taxpayers - current and future - to teach, communicate and assist them in order to foster a "culture of compliance" based on rights and responsibilities, in which citizens see paying taxes as an integral aspect of their relationship with their government.